An Agenda for Studying Credibility Perceptions of Visual Misinformation. (4th March 2023) - Peng, Yilang; Lu, Yingdan; Shen, Cuihua
ABSTRACT: Today's political misinformation has increasingly been created and consumed in visual formats, such as photographs, memes, and videos. Despite the ubiquity of visual media and the growing scholarly attention to misinformation, there is a relative dearth of research on visual misinformation. It remains unclear which specific visual formats (e.g., memes, visualizations) and features (e.g., color, human faces) contribute to visual misinformation's influence, either on their own or in combination with non-visual features and heuristics, and through what mechanisms. In response to these gaps, we identify a theoretical framework that explains the persuasive mechanisms and pathways of visual features in lending credibility (e.g., as arguments, heuristics, and attention determinants). We propose a list of relevant visual attributes to credibility perceptions and a research agenda that integrates methods including computational visual analysis, crowdsourced annotations, and experiments to advance our understanding of visual misinformation.